191k views
5 votes
The nth term of the GP is (-1)^n(2)^n.


( - 1)^(n) (2)^(n)

Find the first three terms.​

User Ian Henry
by
5.3k points

1 Answer

6 votes

Answer:

-2, 4 and -8

Step-by-step explanation:

Given the nth term of a GP expressed as;


a_n = (-1)^n(2)^n

When n = 1


a_1 = (-1)^1(2)^1\\a_1 = -1 * 2\\a_1 = -2\\

when n = 2


a_2 = (-1)^2(2)^2\\a_2 = 1 * 4\\a_2 = 4\\

when n = 3


a_3 = (-1)^3(2)^3\\a_3 = -1 * 8\\a_3 = -8\\

Hence the first three terms of the sequence are -2, 4 and -8

User Pycruft
by
5.9k points